Arsenic efflux and bioremediation potential of Klebsiella oxytoca via the arsB gene - Sana Waqar; Aamira Tariq; Ubaid Ullah; Hira Haleem; Hadiqa Aimen; Sadia Sattar; Nazish Bostan (PLoS ONE, 2025)
Arsenic-resistant Klebsiella oxytoca strain AT-02 was isolated from the ground water of the Multan region of Pakistan. The strain displayed high arsenite and arsenate resistance as minimal inhibitory concentration (MIC) was 600ppm and 10,000ppm respectively. The high tolerance of the isolated strain towards arsenate can be postulated due to significant increase in biofilm in response to arsenate. The bacterial strain exposed to 1/2 and 3/4 MIC showed a significant 10 and 12 folds increase in expression of the arsenite efflux gene arsB. Sequential and structural comparison of the arsB gene showed the presence of conserved arsenic binding residues. Arsenic remediation by AT-02 biomass was 50% after 0.5 hours of incubation and 66% in 2 hours. the increase in remediation efficiency with the increase in incubation time indicates its biosorption potential. the arsenic sensitive strain NK11 showed only 4–5% arsenic remediation. Fourier transform infrared spectroscopy (FTIR) analysis confirmed interaction of arsenate and arsenite with functional groups (aromatic amino acid residues) on the cell surface leading to characteristic peak shifts. Thus, the isolated AT-02 has the potential to remediate both arsenite and arsenate from contaminated environmental sites.